Rethinking University Presidencies in Canadian Higher Education - Lawrence A. White (Ali Khorsandi Taskoh, 2023)
This article discusses the evolving role of university presidents in Canada. The university president is accountable for the successful operation of a university and achieving its strategic goals. The role has become complex due to factors such as the absence of a standard definition of a university, decentralization of funding, and increased competition for student enrollment and research funding. Universities have grown considerably, leading to more diverse and activist populations, larger budgets, and the need for more people to manage internal and external relationships. University presidents must now balance the interests of various stakeholders such as faculty, boards, alumni, governments, and learners. They must also plan for and address the challenges created by system modernization and enterprise technologies, internationalization, campus health and security, changing governments, shifting policy directions, climate change, social justice, and neoliberalism. This article argues that university presidents must possess strong communication skills, impeccable management acumen, and the ability to relate to the evolving realities of learners. This article concludes that the role of university president has evolved from being presiding figures to being accountable leaders who must navigate the complex demands of the modern university system.